JUDGE BIAS IN AESTHETIC GROUP GYMNASTICS - Seppo Suominen (University of Ljubljana Press (Založba Univerze v Ljubljani), 2023)
There are several competitions where the objectivity of judges has raised some questions, in particular the style point evaluation. If part of the actual performance can be objectively measured with an instrument and part of the performance is based on subjective evaluation of judges, an error in ranking is possible. There are some sport disciplines, like ski jumping, where both metrics are used (Krumer et al., 2020); however, in gymnastics, the only criteria are judges' subjective evaluation (Bučar et al., 2012; Leskoŝek et al., 2012; Rotthoff, 2014). Our analysis reveals that biased judging in aesthetic group gymnastics is more than probable in domestic competitions in Finland. The local judge that evaluates their own team is not overestimating the performance in any of its three parts: technical value, artistic value, or execution value. However, it seems that judges strategically underestimate the performance of the most important rival. This underscoring is truncated since the highest and lowest scores are truncated in the case of four judges. The local judge's scoring is usually within the two middle scores, which is taken into account in the final score of a performance. Our analysis used evaluations of 66 different competitions including 585 performances in a period of 22 months. All competitions were domestic, with domestic teams and domestic judges only. Many competitions had 12 judges: 4 evaluating technical value, 4 artistic value, and 4 execution value. All judges were nominated before the actual competition.